IDENTIFICATION PLASTIC BOTTLE BASED ON LIGHTING SYSTEM - Jhosua Arie Swandi; Irsyadi Yani (Indonesian Journal of Engineering and Science (IJES), 2020)
The challenge in waste sorting systems such as plastic bottles is how to identify and classify the types of it. This work aims to build a system of identification and classification of sorting plastic bottles by type. This system uses the Backpropagation method by utilizing a webcam to get colors in the form of Red, Green, and Blue (RGB) color spaces. As light control, three types of lights are used, blue, red, and yellow. The three types of plastics that will be identified are PET, HDPE, and PP. The conclusion from this work is that the percentage of success is 18%, 28%, and 42 for yellow, blue, and red lighting, respectively.